Targeting the Stress System During Gestation: Is Early Handling a Protective Strategy for the Offspring? - Castelli, Valentina; Lavanco, Gianluca; Brancato, Anna; Plescia, Fulvio (Frontiers in Behavioral Neuroscience, 2020)
The perinatal window is a critical developmental time when abnormal gestational stimuli may alter the development of the stress system that, in turn, influences behavioral and physiological responses in the newborns. Individual differences in stress reactivity are also determined by variations in maternal care, resulting from environmental manipulations. Despite glucocorticoids are the primary programming factor for the offspring’s stress response, therapeutic corticosteroids are commonly used during late gestation to prevent preterm negative outcomes, exposing the offspring to potentially aberrant stress reactivity later in life. Thus, in this study we investigated the consequences of one daily s.c. injection of corticosterone (25 mg/kg), from gestational day 14 to 16, and its interaction with offspring early handling, consisting in a brief 15-min maternal separation until weaning, on: i) maternal behavior; ii) behavioral reactivity, emotional state and depressive-like behavior in the adolescent offspring. Corticosterone plasma levels, under non-shock- and shock-induced conditions, were also assessed. Our results show that gestational exposure to corticosterone was associated with a diminished maternal care, impaired behavioral reactivity, increased emotional state and depressive-like behavior in the offspring, associated with an aberrant corticosterone response. The early handling procedure, which resulted in increased maternal care, was able to counteract the detrimental effects induced by gestational corticosterone exposure both in the behavioral- and neurochemical parameters examined. These findings highlight the potentially detrimental consequences of targeting the stress system during pregnancy as a vulnerability factor for the occurrence of an emotional and affective distress in the adolescent offspring. Maternal extra-care proves to be a protective strategy which confers resiliency and restores homeostasis.